COVID-19 Emergency Regulation: How We Survive? - Muhammad Haikal Fathan (Universitas Negeri Semarang, 2020)
At present the country in the world has been destroyed by an outbreak of a disease called the corona virus or another name is covid 19, which is named the equivalent of almost the same type of SARS virus. WHO announced an emergency signal and called on all countries in the world to deal with this virus. In the country of Indonesia various efforts have been made ranging from washing hands, social distancing, forwarding the PSB and so on. Until now, even this virus vaccine. and currently health experts are still trying to find a cure.